Antifungal activity of cotton fabrics finished modified silica-silvercarbon-based hybrid nanoparticles - Igal, Katerine (2018)
In this work, the one-pot sol-gel synthesis of novel siliceous matrixes doped with carbon from spent batteries is reported. The obtained solids with silver nitrate were characterized by their antifungal activity against Aspergillus sp., Cladosporium sp. and Chaetomium globosum, three well-known cellulolytic microorganisms responsible for the deterioration of cotton fabric. In this research it was possible to develop a methodology for the impregnation of cotton fabrics (brin type) and to evaluate the antifungal efficacy. Cotton fabric containing the highest amount of carbon showed the highest antifungal activity against C. globosum and Aspergillus sp. This may be because as the amount of carbon in the silica increases, there is an increase in the surface area that facilitates an effective distribution of the active phase to act, inhibiting the fungal growth.